Circumnuclear multi-phase gas around nearby AGNs investigated by ALMA. Issue Volume 15:Issue S359(2020) (March 2019) - Izumi, Takuma
Abstract: Since the advent of the Atacama Large Millimeter/submillimeter Array (ALMA), more attention has been paid on the ≲100 pc scale circumnuclear disk (CND) to reveal feeding and feedback processes of active galactic nuclei (AGNs). By using cold molecular CO and atomic C0 emission line observations, we have revealed that there are multi-component gas dynamical flows around the AGN of the Circinus galaxy, which may explain the physical origin of the AGN torus. In the luminous Seyfert galaxy NGC 7469, we found that [CI](1–0) line is extraordinary bright relative to CO lines (for example J 2−1), manifesting the physical/chemical influence of the AGN on the surrounding gas in the form of X-ray dominated region (XDR).